2008
DOI: 10.1080/10807030801935009
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Distribution of Cadmium and Nickel in Chronically Exposed Wild Fish: Inferences Regarding Metal Detoxification Strategies and Implications for Setting Water Quality Guidelines for Dissolved Metals

Abstract: The objective of this study was to investigate metal detoxification in chronically exposed juvenile yellow perch (YP: Perca flavescens) and to field test the commonly assumed threshold toxicity model. Fish were collected from lakes located along a cadmium (Cd) and nickel (Ni) concentration gradient. Ambient dissolved metal concentrations were measured to evaluate exposure and total hepatic metal concentrations were determined as a measure of metal bioaccumulation. Hepatic metal partitioning among potentially m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 38 publications
5
25
0
1
Order By: Relevance
“…To regulate the internal availability of essential metals for metabolic functions and to avoid inappropriate binding of essential and non-essential metals to important bio-molecules, various sub-cellular systems have evolved. With this, essential metals in excess of metabolic requirements and non-essential metals are detoxified and/or excreted (Rainbow, 2002;Campbell et al, 2005Campbell et al, , 2008. Excess of metals can be bound to the metal binding protein metallothionein (Vijver et al, 2004;Van Campenhout et al, 2008) and (subsequently) immobilized within granules (Marigómez et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To regulate the internal availability of essential metals for metabolic functions and to avoid inappropriate binding of essential and non-essential metals to important bio-molecules, various sub-cellular systems have evolved. With this, essential metals in excess of metabolic requirements and non-essential metals are detoxified and/or excreted (Rainbow, 2002;Campbell et al, 2005Campbell et al, , 2008. Excess of metals can be bound to the metal binding protein metallothionein (Vijver et al, 2004;Van Campenhout et al, 2008) and (subsequently) immobilized within granules (Marigómez et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Metals have contaminated many lakes in the area, and their effects on fish and invertebrates in the region have been regularly studied since the early 1990s [1][2][3][4]. Research has also demonstrated that the physiology of yellow perch (Perca flavescens) living in these contaminated systems is affected [5][6][7][8]. However, interpreting the causes of these physiological impairments is far from simple.…”
Section: Introductionmentioning
confidence: 97%
“…Research on this topic most commonly refer to Cd, Cu and Zn in various fish species (e.g. in yellow perch (Kraemer et al 2006;Campbell et al 2008); rainbow trout (Kamunde and MacPhail 2008;Sappal et al 2009); zebrafish and roach (Paris-Palacios and BiagiantiRisbourg 2006)), and only sporadically to other elements such as Pb (e.g. in mummichog (Goto and Wallace 2010); brown trout and European eel (Linde et al 1999)), Ni and Tl (e.g. in yellow perch (Campbell et al 2008); fathead minnow (Lapointe and Couture 2009)) and Se (e.g.…”
Section: Introductionmentioning
confidence: 99%